Efficacy of treatment with excimer phototherapy in nail dystrophy secondary to lichen striatus. - Sezer, E.; Kayahan, S. (European Journal of Pediatric Dermatology, 2023)
Nail dystrophy secondary to lichen striatus is rare and difficult to treat. A 4-year-old girl with this problem, who has not responded to topical treatment with clobetasol propionate, is treated with excimer phototherapy which leads to rapid improvement. This treatment, which as far as we know has never been described in the literature, constitutes an effective and safe therapeutic option in cases that do not respond to other topical therapies.